2014
DOI: 10.1111/dom.12307
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of empagliflozin for type 2 diabetes: a systematic review and meta‐analysis

Abstract: Empagliflozin effectively lowers blood glucose and provides additional clinical benefits including body weight and blood pressure reduction. Ongoing trials will elucidate the long-term safety and effect of empagliflozin on cardiovascular outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
144
2
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 188 publications
(165 citation statements)
references
References 39 publications
11
144
2
4
Order By: Relevance
“…The compensatory increase in EGP that occurs with empagliflozin treatment may attenuate the reduction in hyperglycaemia that would be predicted from the increase in UGE, although increases in food intake may also contribute [33]. The observed shift in substrate oxidation from carbohydrate to fat is consistent with the weight loss that has been observed in clinical trials of empagliflozin [14]. The hormonal changes, increased lipolysis and fat oxidation are the metabolic background for the increase in ketone bodies described in a small number of patients receiving SGLT2 inhibitor therapy [34].…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…The compensatory increase in EGP that occurs with empagliflozin treatment may attenuate the reduction in hyperglycaemia that would be predicted from the increase in UGE, although increases in food intake may also contribute [33]. The observed shift in substrate oxidation from carbohydrate to fat is consistent with the weight loss that has been observed in clinical trials of empagliflozin [14]. The hormonal changes, increased lipolysis and fat oxidation are the metabolic background for the increase in ketone bodies described in a small number of patients receiving SGLT2 inhibitor therapy [34].…”
Section: Discussionsupporting
confidence: 63%
“…SGLT2 inhibitors lower fasting and postprandial glycaemia by enhancing urinary glucose excretion (UGE), a mechanism that is independent of insulin secretion [13]. For this reason, SGLT2 inhibitors can be used in association with other antihyperglycaemic agents including dipeptidyl peptidase 4 inhibitors, metformin and insulin [14][15][16]. In particular, empagliflozin as add-on to metformin has been shown to improve HbA 1c and fasting plasma glucose levels for up to 78 weeks [17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…In the meta‐analysis, the incidence of UTIs did not increase with empagliflozin 10 or 25 mg relative to placebo [ORs (95% CI), 1.20 (0.92–1.57) and 1.03 (0.81 to 1.32)] 46. However, genital infections were observed in a greater proportion of patients treated with empagliflozin than in those receiving placebo [ORs (95% CI), 4.39 (2.10–9.19) with 10 mg and 3.31 (1.55–7.09) with 25 mg] 46.…”
Section: Empagliflozinmentioning
confidence: 98%
“…This observation is likely because of caloric loss following glycosuria. In a meta‐analysis of RCTs (10 trials, n  =   6203), empagliflozin 25 mg showed a significant reduction in body weight [weighted mean difference; WMD (95% CI), −1.84 kg (−2.30 to −1.38)] and no increased risk of hypoglycaemia [odds ratio; OR (95% CI), 1.10 (0.87–1.39)] vs. placebo 46.…”
Section: Empagliflozinmentioning
confidence: 99%
“…Older meta-analyses focused on intermediate outcomes of empagliflozin when compared with placebo; e.g., HbA1c, blood pressure, and body weight (7)(8)(9)(10)(11)(12)(13)(14)(15). The most recent high-quality meta-analyses included 13 (6) and 16 (5) randomized controlled trials (RCTs) that reported mortality and morbidity in adults with type 2 diabetes treated with empagliflozin but did not examine the comparative effectiveness of empagliflozin and other specific antidiabetic drugs (5,6).…”
Section: Introductionmentioning
confidence: 99%